2007
DOI: 10.3168/jds.2006-596
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Efficient Dairy Producers Using Data Envelopment Analysis

Abstract: The objective of this research was to calculate the efficiency of a group of Pennsylvania dairy farms to determine factors that contributed to efficiency in production and business management. Data envelopment analysis (DEA) was used to estimate the efficiency. Two models were developed to measure the efficient use of physical (land, cows, and labor) inputs to produce physical (milk and butterfat) outputs, and the use of physical and economic (debt capital) inputs to produce physical and economic (income) outp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
42
1
6

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(50 citation statements)
references
References 11 publications
1
42
1
6
Order By: Relevance
“…In this case, two different DEA models have been applied that focus on natural and economic inputs and outputs. The results obtained verified that it is more important to combine in an efficient context both natural and economic resources than to focus on output maximization and, more specifically, milk maximisation [28]. Regarding the same trend, a similar study identified efficiency scores of different combinations of management practices and feeding [29,30].…”
Section: Introductionsupporting
confidence: 60%
“…In this case, two different DEA models have been applied that focus on natural and economic inputs and outputs. The results obtained verified that it is more important to combine in an efficient context both natural and economic resources than to focus on output maximization and, more specifically, milk maximisation [28]. Regarding the same trend, a similar study identified efficiency scores of different combinations of management practices and feeding [29,30].…”
Section: Introductionsupporting
confidence: 60%
“…A dairy farm's technical efficiency is a measure of the farmer's ability to use production inputs as intensively as possible, and is a necessary condition for profitable farms. During the last few years, several studies (Lawson et al, 2004;Stokes et al, 2007;Hansson and Ö hlmé r, 2008) on dairy farms' technical efficiency present unequivocal results: average performing farms could become more efficient by adjusting to the practices used by the most efficient, best-practice farms. Thus, farms can reduce their use of production inputs and consequently reduce their current production costs, leading to more profitable and long-term sustainable farms.…”
Section: Introductionmentioning
confidence: 99%
“…2009;Coelli et. all 2005., Tauer, 1998Jaforullah and Whiteman, 1999;Stokes et al, 2007;Kumbhakar and Lovell, 2000;Emvalomatis, 2010) in the literature the "multiple input and output measurement".…”
Section: Introductionmentioning
confidence: 99%